Human T cell clones present antigen. - Hewitt, C; Feldmann, M (1989)
Two human T cells clones are described which react with influenza virus hemagglutinin type H3 and synthetic peptides of H3 when presented by PBMC APC. Both T cell clones also responded to peptide Ag in the absence of additional APC suggesting that T cells can simultaneously present and respond to Ag. T cell clones could only present peptide Ag and not an appropriate strain of inactivated whole influenza virus thus indicating an inability to process Ag conventionally. Peptide presentation by T cells was dose dependent, restricted by MHC class II Ag and was dependent on the number of Ag presenting T cells per culture. Experiments with nested peptides showed that the same epitope was recognized in the presence and absence of PBMC APC. No Ag or IL-2 from the propagation procedure was carried over into assays and two-color fluorescence-activated cell sorter analysis of each clone detected no contaminating cells with the phenotype of monocytes, macrophages or B cells; in each T cell clone, all cells expressing MHC class II Ag co-expressed CD3. These date therefore provide strong evidence that human T cell clones can simultaneously present and respond to appropriate forms of Ag.